Pengetahuan, Sikap Ibu Rumah Tangga Mengenai Infeksi Menular Seksual Termasuk Hiv/Aids Serta Perilaku Pencegahannya Di Kelurahan Sanur, Kecamatan Denpasar Selatan, Kota Denpasar Tahun 2013 - Abhinaja, I G Wiswasa (Community Health, 2013)
Sexual transmitted infections (STIs) and HIV/AIDS is one of health problems worldwide particularly in Indonesia. The case of STIs and HIV/AIDS among housewives is related with the knowledge, attitude, and behavior for prevention. This study aims to gain an overview about housewives’ knowledge, their attitude and behavior for prevention of STIs and HIV/AIDS in Sanur village, South Denpasar 2013. This study used descriptive quantitative technique with a cross-sectional approach. Samples of 87 housewives were selected using systematic random sampling. Data was collected from interviews via questionnaire and then analyzed statistically. The results shows that housewives who have high knowledge were 20.7%, moderate 54% and low 25,3%. Knowledge of STIs is related with education; occupation; respondent spouse’s occupation; and number of information resources with p value of each variables was less than 0,05. The respondents who have good attitude were 32.2% and moderate 67.8%. The attitude about STIs and HIV/AIDS is related with occupation, respondent spouse occupation, and number of source information with p value of each was less than 0,05. In addition, behaviors of prevention were 70.5% of wives had sought the treatment in community health center and 40.9% of wives had invited their husband to do medical checkup. Moreover, the other results show that 61.4% of wives had sex with their husband without condom while they experienced STIs symptoms, 13.8% respondents took antibiotics which were purchased without prescriptions and 10.3% respondents took herbal medicine. Respondents who had conducted medical check up to prevent HIV transmission during pregnancy were 29.4%. It can be concluded that knowledge and attitude of housewives are moderate. It is recommended to increase the education about STIs and HIV/AIDS to housewives and their husbands. Moreover, the content of education should be more focuses on knowledge, types, symptom and prevention of STIs and HIV/AIDS.
Keywords: knowledge, attitude, behavior, housewife, STIs, HIV/AIDS